2003
DOI: 10.1046/j.1365-2141.2003.04264.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus infection following unrelated cord blood transplantation for adult patients: a single institute experience in Japan

Abstract: Summary. Cytomegalovirus (CMV) infection in 28 adult patients after cord blood transplantation (CBT) from unrelated donors was compared with that after bone marrow transplantation from HLA (human leucocyte antigen)-matched related (R-BMT) and unrelated (U-BMT) donors. Positive CMV antigenaemia was seen in 19 (79%) of 24 CMV-seropositive patients at a median of 42 d (range 29-85 d) after CBT, but in zero of four CMV-seronegative patients. This did not differ significantly from values observed after R-BMT and U-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
3
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 24 publications
2
58
3
1
Order By: Relevance
“…The shorter time from donor search to transplantation and low steroid therapy requirements for GVHD might be significant factors contributing to this improvement. Although the positive CMV antigenemia rate and incidence of preemptive ganciclovir therapy among CB transplant recipients tended to be higher than among BM transplant recipients, 24 no clinical CMV infection was observed in any recipients after CBT (data not shown), probably because steroids were not required in most cases. A significantly lower incidence of infection as a cause of death in CBT patients was also observed in our series.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The shorter time from donor search to transplantation and low steroid therapy requirements for GVHD might be significant factors contributing to this improvement. Although the positive CMV antigenemia rate and incidence of preemptive ganciclovir therapy among CB transplant recipients tended to be higher than among BM transplant recipients, 24 no clinical CMV infection was observed in any recipients after CBT (data not shown), probably because steroids were not required in most cases. A significantly lower incidence of infection as a cause of death in CBT patients was also observed in our series.…”
Section: Discussionmentioning
confidence: 96%
“…All cord blood grafts were evaluated by HLA-A, HLA-B, and HLA-DRB1 typing and nucleated cell counts. Minor mismatch 11 (24) 20 (29) Major mismatch 18 (40) 28 (41) CMV indicates cytomegalovirus; AML, acute myelogenous leukemia; CR1, CR2, first and second complete remission; Advanced, patients in third complete remission, relapse, CML beyond chronic phase, or who had high-risk cytogenetics were classified as high risk; ALL, acute lymphoblastic leukemia; CML, chronic myelogenous leukemia; CP, chronic phase; MDS, myelodysplastic syndrome; RA, refractory anemia; NHL, non-Hodgkin lymphoma; TBI, total body irradiation; Ara-C, cytosine arabinoside; G-CSF, granulocyte colony-stimulating factor; CY, cyclophosphamide; CsA, cyclosporine; sMTX, short-term methotrexate; FK506, tacrolimus; and mPSL, methylprednisolone.…”
Section: Hla Typing and Donor Selectionmentioning
confidence: 99%
“…Although the incidence of CMV reactivation in our study was lower than that in recent reports of nsTCD haploidentical HSCT, many such studies used detection techniques with greater sensitivity. 42,[44][45][46] However, the CMV reactivation observed was associated with high rates of fatal CMV disease in many such studies; up to 60% of TRM was related to CMV infection and up to 16% of all patients transplanted died from human herpesvirusrelated infections, the majority from CMV. 4,43 In our studies, there was no CMV-related TRM.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators from Japan reported cytomegalovirus (CMV) infection following UCB in 28 adults compared with sibling matched (R-BMT) and URD BM recipients. CMV antigenemia was observed in 19 (79%) of UCB patients at median 42 days [75]. A higher proportion of UCB patients treated with preemptive gancyclovir therapy required a second course of treatment compared with R-BMT and URD BM patients, suggesting that CMV-specific immunity after UCB may be delayed.…”
Section: Ucb Basic Biology and Implications For Immune Reconstitutionmentioning
confidence: 99%